Tā'līm āl-Zhāwāhīr āl-Shāwtīāh Fāwq āl-Qāt'īāh fīī āl-Lughāh āl-Arābīyāh Bāynā Tulāāb Qīsm āl-Lughāh āl-Arābīyāh Jāmī'āh Jānub Shārq Sri Lanka: āl-Wāqīe' wāl Mutāwāqāe' - Shathifa, M.C.S.; Ali, Asem Shehadeh (Al Maghazi : Arabic Language in Higher Education, 2025)
Tamil speaking undergraduates at the Department of Arabic Language, Southeastern University of Sri Lanka, face considerable challenges in comprehending Arabic Suprasegmental phonological phenomena. This study investigates the actual state of students’ phonetic learning and identifies their needs for linguistic improvement. Employing a descriptive-analytical methodology, the research utilizes primary data from questionnaires and semi-structured interviews and secondary data from previous literature. The questionnaire involved 150 students and explored both linguistic background and phonetic learning challenges. Interviews with five lecturers provided qualitative insights. Quantitative data were analyzed via SPSS, and qualitative content analysis was applied. The findings highlight key factors such as individual differences, language interference, curriculum design, lack of practice, and infrastructural limitations. While 70% of students express a desire to study phonetics, obstacles include confusion between phonetics and Tajweed and perceived irrelevance to career prospects. The research emphasizes the negative impact of phonological errors on language proficiency and recommends structured, practice-oriented modules to enhance Arabic phonological skills.